2018
DOI: 10.3177/jnsv.64.229
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Attenuates FOXO1-Target Atrophy Gene Expression in C2C12 Muscle Cells

Abstract: Summary Vitamin D is known to be effective for the prevention of muscle atrophy, such as age-related sarcopenia. However, vitamin D action in skeletal muscle tissue and muscle cells is largely unknown. We previously found that a transcription factor, FOXO1 gene expression, was induced in various muscle atrophy conditions causing muscle atrophy by upregulating atrophy-related genes, including atrogin 1 (ubiquitin ligase) and cathepsin L (lysosomal proteinase). In this study, we found that vitamin D inhibited FO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 17 publications
(23 reference statements)
0
14
0
Order By: Relevance
“…A reporter assay system was prepared with the intention of measuring the transcriptional activity of FOXO1. After screening several compounds derived from various foods and plants, it was found that 1,25(OH) 2 D suppressed the transcriptional activity of FOXO1 [ 59 ]. Moreover, 1,25(OH) 2 D suppressed the increased expression of atrogin-1 and cathepsin L, target genes for FOXO1, which induces muscle atrophy in C2C12 myoblasts [ 59 ] ( Figure 2 ).…”
Section: Mechanism Of Action Of Vitamin D On Skeletal Musclementioning
confidence: 99%
See 1 more Smart Citation
“…A reporter assay system was prepared with the intention of measuring the transcriptional activity of FOXO1. After screening several compounds derived from various foods and plants, it was found that 1,25(OH) 2 D suppressed the transcriptional activity of FOXO1 [ 59 ]. Moreover, 1,25(OH) 2 D suppressed the increased expression of atrogin-1 and cathepsin L, target genes for FOXO1, which induces muscle atrophy in C2C12 myoblasts [ 59 ] ( Figure 2 ).…”
Section: Mechanism Of Action Of Vitamin D On Skeletal Musclementioning
confidence: 99%
“…After screening several compounds derived from various foods and plants, it was found that 1,25(OH) 2 D suppressed the transcriptional activity of FOXO1 [ 59 ]. Moreover, 1,25(OH) 2 D suppressed the increased expression of atrogin-1 and cathepsin L, target genes for FOXO1, which induces muscle atrophy in C2C12 myoblasts [ 59 ] ( Figure 2 ). Interestingly, Yang et al recently reported that physical inactivity and low serum vitamin D can synergistically promote sarcopenia in the elderly [ 60 ].…”
Section: Mechanism Of Action Of Vitamin D On Skeletal Musclementioning
confidence: 99%
“…Low vitamin intake is reportedly related to the risk of frailty in older people [14]. In particular, the role of vitamin D, a fat-soluble vitamin, in sarcopenia has been increasingly reported [15][16][17]. Regulation of bone homeostasis is also the role of vitamin D [16].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the role of vitamin D, a fat-soluble vitamin, in sarcopenia has been increasingly reported [15][16][17]. Regulation of bone homeostasis is also the role of vitamin D [16]. An epidemiological study suggested that usage of vitamin D was effective for the prevention of decreased muscle mass [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation